Tożsamość polityczna Edith Stein. Próba rekonstrukcji - GNIAZDOWSKI, Andrzej (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2013)
The article focuses on the signifi cance of the issue of political identity in the early thought of Edith Stein. The motivation behind this project was the author’s belief that the issue in question must have been among Edith Stein’s theoretical interests since the central theme of her philosophical investigations was the structure of the human person. The objective of the present considerations is to demonstrate that Stein’s refl ections included in her work An Investigation Concerning the State are guided by the fundamental question about the meaning of the belonging of the human being in the «world of the spirit» in the sense Husserl attributed to this category in the second volume of his Ideas Pertaining to a Pure Phenomenology and to a Phenomenological Philosophy. An attempt at the reading of Stein’s Investigation Concerning the State with a view to exploring the signifi cance of the problem of political identity in it involves an interpretation of this work in the context of her earlier studies: On the Problem of Empathy, Sentient Causality, and Individual and Community, in which she analyzed the questions of the structure and identity of the human person. The article demonstrates a twofold attempt: to explore the political identity of Edith Stein herself and to analyze the shaping of her political consciousness on the basis of her autobiographical writings and her letters. In order to bring out the theoretical foundations of Stein’s Investigation Concerning the State, as well as to describe the relation between the problems she discusses there and the analysis of the human person she advanced elsewhere, the biographical context of her research is characterized. Translated by Dorota Chabrajska